2022
DOI: 10.1038/s41467-022-33087-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic and steric effects underlie acetylation-induced changes in ubiquitin structure and function

Abstract: Covalent attachment of ubiquitin (Ub) to proteins is a highly versatile posttranslational modification. Moreover, Ub is not only a modifier but itself is modified by phosphorylation and lysine acetylation. However, the functional consequences of Ub acetylation are poorly understood. By generation and comprehensive characterization of all seven possible mono-acetylated Ub variants, we show that each acetylation site has a particular impact on Ub structure. This is reflected in selective usage of the acetylated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 84 publications
1
7
0
Order By: Relevance
“…Using NMR, acetylation of ubiquitin at specific Lys residues was shown to enable ubiquitin to adopt distinct conformations that modulated its binding properties, leading to acetylation-site-specific ubiquitin interactomes. Acetylation at different Lys residues of ubiquitin also hampered the capacity of several E3s to undergo autoubiquitylation 158 .…”
Section: Ubiquitylation Beyond Lysmentioning
confidence: 99%
“…Using NMR, acetylation of ubiquitin at specific Lys residues was shown to enable ubiquitin to adopt distinct conformations that modulated its binding properties, leading to acetylation-site-specific ubiquitin interactomes. Acetylation at different Lys residues of ubiquitin also hampered the capacity of several E3s to undergo autoubiquitylation 158 .…”
Section: Ubiquitylation Beyond Lysmentioning
confidence: 99%
“…However, a few examples showed that glutamine does not faithfully represent the property changes following the acetylation. [127,[135][136][137] By taking advantage of the high-fidelity and site-specificity of GCE-enabled incorporation, five lysine acetylation sites in the small GTP-binding protein Ran were studied using monoacetylated full-length proteins. [123] Results from the study revealed how the acetylation at a specific position in Ran impacts its interaction with the guanine exchange factor RCC1 and its essential functions, such as nucleotide hydrolysis, binding to import and export receptors.…”
Section: Acetyl-lysine (Ack) and Analogsmentioning
confidence: 99%
“…Results from the study revealed how the acetylation at a specific position in Ran impacts its interaction with the guanine exchange factor RCC1 and its essential functions, such as nucleotide hydrolysis, binding to import and export receptors. The GCE‐enabled method was also adapted in the first comprehensive report on lysine acetylation in ubiquitin (Ub) [127] . As one major type of PTM, how ubiquitination is regulated through lysine acetylation of Ub was not well understood.…”
Section: Acetyl‐lysine (Ack) and Analogsmentioning
confidence: 99%
See 2 more Smart Citations